Navigating Water Sustainability in Mineral Mining with a Systems Thinking-Based Approach - Respati, Gilrandy; Putro, Utomo Sarjono (International Journal Labs, 2023)
This paper provides a comprehensive review and analysis of the sustainable management of water resources in the mining industry. It presents an overview of various sustainable development frameworks for the mining sector, emphasizing the need for a more comprehensive and integrative approach to managing water resources. The paper also highlights the critical role of water in mining operations and the increasing pressure on water resources due to mining activities. Consequently, it underscores the significance of sustainable water management practices such as stakeholder engagement, catchment-based approaches, and adequate water management strategies. The researcher combined a qualitative approach with a methodology for conducting a literature review. The majority of the articles and other sources used to compile the study's data were books and academic publications that examined relevant subjects (Water sustainability, mineral mining, system thinking-based approach). The study advocates for a shift from traditional mechanistic models and linear thinking to a more holistic systems thinking approach for addressing the complex environmental challenges associated with water resources management in mining. Furthermore, it presents system dynamics modeling as a promising tool for understanding and predicting the behavior of complex water resource systems and devising appropriate strategies for sustainable outcomes. A conceptual framework for sustainable underground mine water management is proposed through a synthesis of previous studies. The framework integrates systems thinking and sustainability principles, paving the way for socially equitable, environmentally sustainable, and economically beneficial water management strategies in the mining industry.